Myocardial perfusion by contrast echocardiography. Establishment of normal pattern of intracoronary injection and safety in humans - Morcerf,Fernando (1999)
OBJECTIVE: To establish the normal pattern and safety of echocardiographic contrast in patients with no significant obstruction of epicardial coronary arteries. METHODS: 67 patients with normal coronary arteries or obstructions < 50% were selected from 277 patients who underwent coronary angiography (CA). Mean age was 56 ± 11years and 36 were males. At the end CA, echocardiographic contrast was selectively injected into each coronary artery. The parasternal short axis of the left ventricle (LV) was divided into six segments: anterior (A), antero-lateral (AL), postero-lateral (PL), posterior (P), infero-septal (IS) and antero-septal (AS). Anterolateral (ALPM) and posteromedial papillary muscles (PMPM) were also considered. The pattern and intensity of the appearance of the myocardial contrast was visually analyzed. RESULTS: The right coronary artery (RCA) was dominant in 60 patients. Contrast appearance was sudden and simultaneous in the 3 muscle layers. All segments could be contrasted after the injection in both coronary arteries. 100% of the AS, A and AL segments, 97% of the PL and 98% of the ALPM were perfused by the left coronary artery (LCA). P and IS segments were perfused by the RCA in 85% and 82%, respectively, and by a dominant LCA in 71% of the cases. The PMPM was perfused by a dominant RCA in 77% and by a dominant LCA in 86%. There were no symptoms. CONCLUSION: Intracoronary injection of the sonicated solution is a safe procedure that allows for an excellent opacification of the myocardium and can potentially be used during routine CA.